Early allergen exposure and atopic eczema - Harris, J.M.; Williams, H.C.; White, C; Moffat, S; Mills, A.J.; Newman, Taylor; Cullinan, P (Blackwell Publishing, 2007)
Background The relationship between exposure to indoor aeroallergens in early life and subsequent eczema is unclear. We have previously failed to show any significant associations between early life exposure to house dust mite and cat fur allergens and either sensitization to these allergens or wheeze. We have also previously reported a lower prevalence of parent-reported, doctor-diagnosed eczema by age 2 years for children exposed to higher concentrations of house dust mite, but no other associations with other definitions of eczema or for exposure to cat allergen. Objectives To extend the exposure–response analysis of allergen exposure and eczema outcomes measured up to age 8 years, and to investigate the role of other genetic and environmental determinants. Methods A total of 593 children (92Æ4% of those eligible) born to all newly pregnant women attending one of three general practitioner surgeries in Ashford, Kent, were followed from birth to age 8 years. Concentrations of house dust mite and cat allergen were measured in dust samples collected from the home at 8 weeks after birth. The risk of subsequent eczema as defined by the U.K. diagnostic criteria was determined according to different levels (quintiles) of allergen exposure at birth. Results By age 8 years, 150 (25Æ3%) children had met the diagnostic criteria for eczema at least once. Visible flexural dermatitis was recorded at least once for 129 (28Æ0%). As in other studies, parental allergic history was positively associated with most eczema outcomes, as were higher maternal education and less crowded homes. No clear linear associations between early exposure to house dust mite or cat allergen were found, regardless of the definition of eczema used. The risk of eczema appeared to increase for the three lowest quintiles of house dust mite allergen exposure (odds ratio, OR 1Æ37 for third quintile compared with first), and then to fall for the two highest quintiles (OR 0Æ66 and 0Æ71) even after controlling for confounding factors. Conclusions The lack of any clear exposure–disease relationship between allergens in early life and subsequent eczema argues against allergen exposure being a major factor causing eczema. If the lower levels of eczema at higher levels of house dust mite are confirmed, then interventions aimed at reducing house dust mite in early infancy could paradoxically increase the risk of subsequent eczema.